Innovaciones tecnológicas en agroecosistemas de piña (Ananas comosus) en el Ecuador - Ube Guerrero, Victor Enrique (2024)
This document seeks to inform about the importance of the use of technological innovations in pineapple cultivation agroecosystems to improve production and quality, understanding the economic benefits that these applications of these systems will bring us and the favorable knowledge for We will learn how interesting technological innovations are and how valuable they are for farmers. We will also learn about the main technological innovations, which help maintain a crop in good condition. Technological innovations in pineapple cultivation offer advanced tools to improve efficiency and agricultural productivity. These include sensors for monitoring soil and plants, drones for remote sensing, smart irrigation systems, precision agriculture, genetic improvement and agricultural robotics. These technologies enable more precise management of resources, early detection of problems, and reduced reliance on manual labor. By adopting these innovations, farmers can improve crop quality, reduce costs, and promote more sustainable agricultural practices.